Pengaruh Kompetensi, Komitmen Organisasi dan Budaya Organisasi Terhadap Organizational Citizenship Behavior - Cokorde Gede Putra Yudistira; Ni Nyoman Supiatni; I Ketut Muderana; I Gusti Ayu Agung Utami Cahaya Putri (STIMI Handayani Denpasar, 2023)
The purpose of this study was to determine the partial and simultaneous influence and the level of competence, organizational commitment and organizational culture on Organizational Citizenship Behavior at PT. Angkasa Pura I (Persero) Ngurah Rai International Airport, Bali. This research is quantitative. Sources of data in this study using primary data and secondary data. Primary data in the form of data obtained through distributing questionnaires to 234 respondents as research samples and secondary data in the form of company general description data. The statistical analysis used in this study is multiple linear regression. The result of this research is that competence has a significant positive effect on Organizational Citizenship Behavior. This shows that the better the competence in the company, the higher the OCB felt by employees. Organizational Commitment has no significant effect on OCB. This shows that the good or bad organizational commitment of employees in the company will not affect the increase or decrease in the OCB of employees at PT. Angkasa Pura I (Persero) Ngurah Rai International Airport, Bali. Organizational culture has a significant positive effect on OCB. This shows that the better the organizational culture in the company, the higher the OCB felt by employees.